Fas and FasL genetic polymorphisms in women with recurrent pregnancy loss: a case-control study. (3rd July 2019) - Han, Ae Ra; Choi, Young Min; Hong, Min A; Kim, Jin Ju; Lee, Sung Ki; Yang, Kwang Moon; Paik, Eun Chan; Jeong, Hyeon Jeong; Jun, Jong Kwan
Abstract: Aberrant apoptosis at the trophoblast–maternal interface and abnormal expression of Fas and Fas ligand (FasL) have been reported in complicated pregnancies with recurrent pregnancy losses (RPL) and preeclampsia. We assessed the prevalence of Fas and FasL genetic polymorphisms in Korean women with RPL and in fertile controls. In total, 306 women with RPL and 298 fertile controls were enrolled. Genotype distributions of Fas and FasL in RPL patients versus fertile controls were examined under the Hardy–Weinberg equilibrium. Fas −670 A/G genotype (AA versus AG versus GG, p  = 0.340) and allele frequencies (A versus G, p  = 0.412) were not different between the RPL and control groups. There was no difference in each Fas −1377 G/A and FasL −844 C/T genotype, and their allele frequencies. In addition, the unions of two zygosities of each genotype and their combined genotypes did not differ between two groups. No difference in the prevalence of Fas and FasL single-nucleotide polymorphisms (SNPs) was observed between women with RPL and fertile controls among Korean women. To determine the possibility of genetic polymorphisms in Fas and its ligand as risk factors for RPL, further studies in various races and a large study population are needed.